DIMENSI KUALITAS PELAYANAN PUBLIK KANTOR KECAMATAN LOA JANAN - Lestari, Ipana; Utomo, Heryono Susilo; Amin, Jamal (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
This article aims to describe and analyze the quality of public services at the Loa Janan District Office, particularly in licensing services, as well as to identify the supporting and inhibiting factors. Utilizing a qualitative approach, this study collected data through interviews, observations, and documentation, which were subsequently analyzed using an interactive data analysis model. The findings indicate that the overall quality of licensing services at the Loa Janan District Office is generally good, supported by five main dimensions. In the dimension of physical evidence, facilities and staff appearance are adequate; however, friendliness and communication completeness require improvement. In the reliability dimension, services are generally accurate and timely, although there are occasional delays and a need for more comprehensive information. In the responsiveness dimension, staff are highly responsive and communicative, with smooth processes. In the assurance dimension, services at the Loa Janan District Office demonstrate high levels of security, staff competence, and public trust. In the empathy dimension, staff exhibit significant empathy, enhancing resident satisfaction and trust in the district government.